2021
DOI: 10.1111/gcb.15903
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing past thermal conditions in beach microclimates

Abstract: Reconstruction of past conditions provides important information on how ecosystems have been impacted by climate change, but generally for microhabitats worldwide there are no long-term empirical measurements. In these cases, there has been protracted debate about how various large-scale environmental proxies can best be used to reconstruct local temperatures. Here we help resolve this debate by examining how well environmental proxies hindcast sand temperatures at nest depths for five sea turtle nesting sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…In corroboration with previous studies (e.g. Fuentes et al, 2009; Laloë et al, 2021), we showed that AT is strongly correlated with sand temperatures at the nest depth on sea turtle nesting beaches. There are likely several reasons for the residual variation on plots of sand temperature explained by environmental proxies.…”
Section: Discussionsupporting
confidence: 93%
“…In corroboration with previous studies (e.g. Fuentes et al, 2009; Laloë et al, 2021), we showed that AT is strongly correlated with sand temperatures at the nest depth on sea turtle nesting beaches. There are likely several reasons for the residual variation on plots of sand temperature explained by environmental proxies.…”
Section: Discussionsupporting
confidence: 93%
“…Previous work has shown that SST and air temperature (AT) measured over large scales near nesting sites are tightly correlated with sand temperature at nest depths [ 48 51 ]. More recently it was shown that the gradients of these relationships are consistent across sites, and that for every 1°C increase in AT, sand temperature at nest depth increases by an average 0.86°C (standard deviation = 0.26°C, n = 36; [ 52 ]). Similarly, for every 1°C increase in SST, sand temperature increases by an average 0.72–0.83°C [ 48 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently it was shown that the gradients of these relationships are consistent across sites, and that for every 1°C increase in AT, sand temperature at nest depth increases by an average 0.86°C (standard deviation = 0.26°C, n = 36; [ 52 ]). Similarly, for every 1°C increase in SST, sand temperature increases by an average 0.72–0.83°C [ 48 , 52 ]. In other words, because of the tight positive relationship between SST and sand temperature it is very likely that if SST rises at one site, so will sand temperature at nest depth.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from nesting sites across the world have shown that air temperatures in the 4° by 4° quadrats reflect sand temperatures at nest depth at nesting sites (e.g. Esteban et al, 2016;Hays et al, 2003) and typically a 1°C increase in air temperature equates to a 0.86°C increase in sand temperature at nest depth (Laloë, Chivers, et al, 2021). We obtained air temperatures for 1° by 1° boxes and calculated a mean monthly air temperature for each 4° by 4° quadrat weighing values by the number of observations in each 1° by 1° quadrat.…”
Section: Air Temperature Recordsmentioning
confidence: 99%
“…Air temperatures have repeatedly been shown to be closely linked to sand temperatures at sea turtle nest depth, including studies at nesting beaches in Ascension Island (South Atlantic; Hays et al, 2003), the Chagos Archipelago (Indian Ocean; Laloë, Chivers, et al, 2021), in Florida (West Atlantic; Hawkes et al, 2007) and around Australia (South Pacific; Fuentes et al, 2009Fuentes et al, , 2010. Predictions of sand temperatures from sand versus air temperature models have been shown to be close to measured sand temperatures (Laloë et al, 2017;Laloë, Chivers, et al, 2021) and so air temperature has been used many times as a proxy for predicting likely temporal changes in mean incubation temperatures at nest depths across decades (e.g. Fuentes et al, 2009Fuentes et al, , 2010Hawkes et al, 2007;Jensen et al, 2018;Laloë, Chivers, et al, 2021).…”
mentioning
confidence: 99%